Implementation and Performance Analysis of Remote Inclination Monitoring System - Gürkan, Koray; Akpınar, Burak; Dındar, Ahmet Anıl (My University, 2021)
This paper presents design, implementation, and test stages of internet based inclinometer system. MEMS based two-axis inclinometer sensor, isolated data acquisition board, Raspberry Pi based microcomputer, and remote FTP server are the main parts of the system. Verification, noise characterization with Allan deviation, and temperature dependency measurements are conducted. Compensation and signal processing algorithms are performed in Google Colab. Long-term test on a high-rise building have revealed that the inclinometer system is suitable for structural health monitoring applications.
Keywords: Analog-digital conversion; MEM/NEMS; Time-Domain Measurements; Data Acquisition; Sensors: Inertial